The Influence of Net Profit Margin, Dividend Payout Ratio, and Total Asset Turnover on Sharia Share Prices in Jakarta Islamic Index - Mustafa, Ahmad Wildan Adiansyah; Purwohedi, Unggul; Utaminingtyas, Tri Hesti (Jurnal Akuntansi, Perpajakan dan Auditing, 2022)
This study was conducted to determine whether there is an effect of using the ratio of NPM, TATO, and DPR on Sharia Stock Prices in the Jakarta Islamic Index during the 2016 – 2019 period with or without the control variable of industry type. The use of this variable aims to describe the condition of the company fundamentally that can affect the price of sharia shares in JII. The type of industry used as the control variable uses the dummy variable method on sharia stock prices in the Jakarta Islamic Index (JII) for the 2016-2019 period. The research method used in this study is quantitative. The selection of research samples using the purposive sampling technique. The results of this study are the net profit margin has no effect on stock prices with or without industrial type control variables, and the dividend payout ratio has no effect on stock prices with or without industrial type control variables. total asset turnover has a positive effect on stock prices with or without industrial type control variables.